Sustainable development? dam construction and the marginalization of civil society. Case of Sondu Miriu. - Moreri, Keletso (My University, 2010)
The impact of dam construction can have devastating results on the livelihoods of communities dependent on the river. Consequently, not everyone may be supportive of the project. As the poor and marginalised rely on civil society due to lack of political and economical influence, civil associations have become a sight of democracy and a promise of sound sustainable development. Thus, if civil society is weak which is often the case in sub-Saharan Africa, the needs of the most neglected peoples may be neglected in development projects. By looking at the proceedings between of civil society, the political elite and other international agencies, attitudes around fair and sustainable development is revealed through dam construction stages.